EFEKTIVITAS PERAWATAN LUKA MENGGUNAKAN NACL 0,9% PADA Ny.P IBU POST PARTUM NORMAL PRIMIPARA DENGAN INDIKASI RUPTURE PERINEUM DI DESA KALIGONDANG - Niken Risma Astika; Priyatin Sulistiowati; Dwi Astuti (PT. Jurnal Center Indonesia Publisher, 2025)
On a world scale, the main cause of high maternal mortality is post-partum infection. Of the 500 million incidents of postpartum infections, there are 75,000 deaths, in Purbalingga the incidence of perineal infections will reach 5.7% in 2023. One of the factors is the high rate of postpartum infections, namely low knowledge about infection prevention. One effective management is perineal wound care using NaCl 0.9%. This study aims to determine the effectiveness of wound treatment using 0.9% NaCl in normal primiparous post partum mothers with indications of perineal rupture in Kejobong Village. This research uses a qualitative method with a case study approach. After treating the wound twice for 3 days using 0.9% NaCl, it was found that the wound looked better and there were no signs of infection as indicated by a decrease in the REEDA score from 11 categories of unhealed wounds to 2 categories of moderate wounds. This is supported by cleanliness of the wound area and choosing the right food. Wound treatment using 0.9% NaCl is effective for healing perineal ruptures.